Accelerated maturation of Tk‐subtilisin by a Leu→Promutation at the C‐terminus of the propeptide, which reduces the binding of the propeptide to Tk‐subtilisin. (11th January 2013) - Uehara, Ryo; Ueda, Yasunori; You, Dong‐Ju; Koga, Yuichi; Kanaya, Shigenori
<x xml:space="preserve">Abstract</x> Tk‐subtilisin, a subtilisin homologue (Gly70‐Gly398) from Thermococcus kodakarensis, is matured from its precursor, Pro‐Tk‐subtilisin [Tk‐subtilisin in a pro form (Gly1‐Gly398)], by autoprocessing and degradation of propeptide [Tk‐propeptide, a propeptide of Tk‐subtilisin (Gly1‐Leu69)]. The scissile peptide bond between Leu69 and Gly70 of Pro‐Tk‐subtilisin is first self‐cleaved to produce an inactive Tk‐propeptide:Tk‐subtilisin complex, in which the C‐terminal region of Tk‐propeptide binds to the active‐site cleft of Tk‐subtilisin. Tk‐propeptide is then dissociated from Tk‐subtilisin and degraded by Tk‐subtilisin to release active Tk‐subtilisin. To examine whether the mutation of Leu69 to Pro, which is the most unfavourable residue in the P1 position for subtilisins, affects the maturation of Pro‐Tk‐subtilisin, the Pro‐Tk‐subtilisin and Tk‐propeptide derivatives with this mutation (Pro‐L69P and L69P‐propeptide) were constructed and characterized. Pro‐L69P was autoprocessed more slowly than Pro‐Tk‐subtilisin. Nevertheless, it matured to Tk‐subtilisin more rapidly than Pro‐Tk‐subtilisin because L69P‐propeptide was degraded by Tk‐subtilisin more rapidly than Tk‐propeptide. The chaperone function and stability of L69P‐propeptide were comparable to those of Tk‐propeptide, whereas the inhibitory potency and binding ability of L69P‐propeptide were considerably reduced compared to those of Tk‐propeptide. The crystal structure of the complex between L69P‐propeptide and S324A‐subtilisin (i.e. a protease activity‐defective mutant) revealed that the C‐terminal region of L69P‐propeptide does not well fit into the substrate binding pockets of Tk‐subtilisin (S1–S4 subsites) as a result of a conformational change caused by the mutation. These results suggest that the Leu→Pro mutation accelerates the maturation of Pro‐Tk‐subtilisin by reducing the binding ability of Tk‐propeptide to Tk‐subtilisin. Database The coordinates and structure factors have been deposited in the RCSB Protein Data Bank under ID code: 3VV2. Structured digital abstract Pro-Tk-subtilisin and Pro-Tk-subtilisin cleave by enzymatic study (View interaction) L69P-propeptide and S324A-subtilisin bind by x-ray crystallography (View interaction) Tk-propeptide binds to S324A-subtilisin by surface plasmon resonance (View interaction)